1995
DOI: 10.1037/0278-7393.21.6.1595
|View full text |Cite
|
Sign up to set email alerts
|

Intrusive cognitions: An investigation of the emotional Stroop task.

Abstract: The role of intrusive cognitions was investigated using the emotional Stroop effect, in which irrelevant threat-related words interfered more with color naming than neutral words. In Experiment 1, the emotional Stroop effect decreased over blocks, indicating habituation. In Experiment 2, the interference persisted when different words were used in each block, suggesting that the habituation occurred at the level of the individual stimulus. However, there was some evidence for a decline in interference, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
204
1
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(232 citation statements)
references
References 73 publications
22
204
1
5
Order By: Relevance
“…Negatively valent auditory distractors impaired serial recall of visually presented words more than neutral or irrelevant distractors did. These results run parallel to research that, using the Stroop task, showed that negativetrait adjectives delayed the naming of the color in which they were printed more than neutral words did, which has been interpreted to suggest that valent-trait adjectives may automatically attract and consume attention at the expense of resources available to concurrent cognitive processes (McKenna & Sharma, 1995;Pratto & John, 1991;Williams et al, 1996; see also Algom et al, 2004;McKenna & Sharma, 2004). This is to be expected because valenttrait adjectives carry meaning in that they provide information about the state of the environment that requires attention.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Negatively valent auditory distractors impaired serial recall of visually presented words more than neutral or irrelevant distractors did. These results run parallel to research that, using the Stroop task, showed that negativetrait adjectives delayed the naming of the color in which they were printed more than neutral words did, which has been interpreted to suggest that valent-trait adjectives may automatically attract and consume attention at the expense of resources available to concurrent cognitive processes (McKenna & Sharma, 1995;Pratto & John, 1991;Williams et al, 1996; see also Algom et al, 2004;McKenna & Sharma, 2004). This is to be expected because valenttrait adjectives carry meaning in that they provide information about the state of the environment that requires attention.…”
Section: Discussionsupporting
confidence: 67%
“…It is known that in Stroop tasks, valent words delay the naming of the color in which they are printed more than neutral words do. This has been interpreted to show that valent words attract attention at the expense of resources available to other cognitive processes (McKenna & Sharma, 1995;Pratto & John, 1991;Williams, Mathews, & MacLeod, 1996; see also Algom, Chajut, & Lev, 2004;McKenna & Sharma, 2004). Similarly, valent auditory distractors may attract more attention than neutral auditory distractors at the expense of resources available for serial recall.…”
mentioning
confidence: 99%
“…However, the output position percentile for taboo words (M 55.8%) was numerically, but not significantly, larger than the output percentile for neutral words (M 52.2%) [F(1,32) Experiment 1B. We were concerned that the participants in the between-subjects design might habituate to taboo words over the series of 160 color-naming trials (see McKenna & Sharma, 1995). To address this concern, the color-naming times were broken into two blocks of 80 trials.…”
Section: Resultsmentioning
confidence: 99%
“…The practice block used neutral words that were different from the neutral words presented in Blocks 1 and 2. In Block 1, 25 threat-related and 25 neutral words randomly selected from McKenna and Sharma (1995) 1 , as well as 25 sexual words and 25 school words, were each presented once. (The words used here, along with the mean valence rating, mean arousal rating, and mean parity RT for each word, are available at the Psychonomic archive, www.psychonomic.org/archive.)…”
Section: Designmentioning
confidence: 99%
“…Most of the sexually explicit words were selected from the word set used by Anderson (2005). Attentional capture by emotional stimuli may not be the result of the emotionality of the stimuli per se, but of the fact that the emotional stimuli form a tighter category than do random neutral words (McKenna & Sharma, 1995). To address this issue, as well as the literature suggesting that participants may be distracted by concernrelevant stimuli (Dalgleish, 1995;Williams et al, 1996), we added a control category of school words, which not only form a single category but are also concern relevant to our sample of undergraduate students.…”
Section: The Present Investigationmentioning
confidence: 99%